Building Bonds: The Transition from Teamwork to Friendship in Engineering Education and its Influence on the Well-being of Female Students - Moreno, Sandra Cruz; Chance, Shannon (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This paper explores the lived experiences of female students implementing collaborative project/problem- based learning (PBL) within undergraduate engineering programmes at TU Dublin, in Ireland. The paper emphasises the significance of teamwork in promoting meaningful connections among students that can result in gender inclusivity. Drawing on a longitudinal dataset of 32 interviews with 13 female engineering students, the research adopts a phenomenological approach to investigate how team dynamics evolved over time. The findings reveal that early challenges often led to feelings of exclusion. However, as peer trust developed, many students transitioned from feeling isolated to forming meaningful friendships, especially with other women. These friendships provided emotional support, mutual recognition, and academic motivation. The findings reveal that developing such friendships helped students feel valued and understood, navigate gendered barriers, and promote persistence in the engineering discipline. Through this lens, we gain insights into the dynamics of teamwork and its interplay in shaping students' emotional well-being. This study underscores the need for greater institutional efforts to support peer connection and inclusive team environments. Ultimately, this research advocates for a culture of care within engineering education that prioritises inclusivity and emotional well-being as essential components of student success.